Experiences of Accessing and Providing Contraceptive Implant Removal Services in Gaborone, Botswana: A Qualitative Study Among Implant Users and Healthcare Providers - Howett, Rebecca; Krogstad, Emily A.; Badubi, Opelo; Gertz, Alida M.; Bawn, Caitlin; Mussa, Aamirah; Kgaswanyane, Tiroyaone; Malima, Sifelani; Maotwe, Tshego; Mokganya, Lesego; Ramogola-Masire, Doreen; Morroni, Chelsea (Frontiers in Global Women's Health, 2021)
Introduction: This study explored implant user and healthcare provider experiences of accessing and providing contraceptive implant removal services in Gaborone, Botswana, following introduction of the implant in the public sector in 2016. We sought to understand reasons for satisfaction and dissatisfaction with services and their potential impact on wider perceptions of the implant, including influence on future uptake. Methods: Qualitative data were collected through in-depth interviews. Participants comprised ten women who had previously undergone implant removal, and ten providers whose work included provision of implant insertion and removal. Data were analyzed using thematic content analysis. Results: Seven of the ten users in this study had experienced a delay between initial request and undergoing implant removal. This interval ranged from <1 week to 3 months. Users identified the principal barriers to accessing implant removal services as lack of access to trained removal providers, inconvenient appointment times, and provider resistance to performing removal. Nine of the ten providers in this study had experienced barriers to providing implant removal, including insufficient training, lack of equipment, lack of time, and lack of a referral pathway for difficult removals. Despite experiencing barriers in accessing removal, users' perceptions of the implant remained generally positive. Providers were concerned that ongoing negative user experiences of removal services would damage wider perceptions of the implant. Conclusion: Introduction of the contraceptive implant in Botswana has been an important strategy in increasing contraceptive choice. Following an initial focus on provision of insertion services, the development of comparable, accessible removal services is critical to ensuring that the implant remains a desirable contraceptive option and is vital to upholding women's reproductive health rights. The experiences of users and providers in this study can inform the ongoing development of services for implant insertion and removal in Botswana and other lower-resource settings.